Sustaining nitrogen dynamics: A critical aspect for improving salt tolerance in plants - Nazir, Faroza; Mahajan, Moksh; Khatoon, Sayeda; Albaqami, Mohammed; Ashfaque, Farha; Chhillar, Himanshu; Chopra, Priyanka; Khan, M. Iqbal R. (Frontiers in Plant Science, 2023)
In the current changing environment, salt stress has become a major concern for plant growth and food production worldwide. Understanding the mechanisms of how plants function in saline environments is critical for initiating efforts to mitigate the detrimental effects of salt stress. Agricultural productivity is linked to nutrient availability, and it is expected that the judicious metabolism of mineral nutrients has a positive impact on alleviating salt-induced losses in crop plants. Nitrogen (N) is a macronutrient that contributes significantly to sustainable agriculture by maintaining productivity and plant growth in both optimal and stressful environments. Significant progress has been made in comprehending the fundamental physiological and molecular mechanisms associated with N-mediated plant responses to salt stress. This review provided an (a) overview of N-sensing, transportation, and assimilation in plants; (b) assess the salt stress-mediated regulation of N dynamics and nitrogen use- efficiency; (c) critically appraise the role of N in plants exposed to salt stress. Furthermore, the existing but less explored crosstalk between N and phytohormones has been discussed that may be utilized to gain a better understanding of plant adaptive responses to salt stress. In addition, the shade of a small beam of light on the manipulation of N dynamics through genetic engineering with an aim of developing salt-tolerant plants is also highlighted.